2018
DOI: 10.1111/jgh.14054
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and gallbladder diseases: A retrospective study

Abstract: Helicobacter pylori infection was related with cholecystic polypus and gallstones in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Many studies have shown that H. pylori and enterohepatic strains of Helicobacter contribute to the formation of cholesterol gallstones [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. H. pylori is a Gram-negative, spiral-shaped, motile microorganism.…”
Section: Helicobacter Pylori and Helimentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that H. pylori and enterohepatic strains of Helicobacter contribute to the formation of cholesterol gallstones [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. H. pylori is a Gram-negative, spiral-shaped, motile microorganism.…”
Section: Helicobacter Pylori and Helimentioning
confidence: 99%
“…A retrospective study performed in Beijing (7803 subjects) revealed that the prevalence of gallstones in the group of H. pylori (+) individuals was 1.53 times lower than in the group of H. pylori (-) ( p = 0.012) [ 58 ]. Another study showed the absence of a clear link between GSD and the colonization of human gallbladder tissue by Helicobacter in the Mexican population [ 76 ].…”
Section: Helicobacter Pylori and Helimentioning
confidence: 99%
“…The same study identified a significant relationship between gallbladder polyps and H. pylori -positivity. 25 Helaly et al. 26 reported a significant relationship between H. pylori -positivity in the stomach and the gallbladder, while another study also found a strong association between gallbladder and stomach H. pylori -positivity.…”
Section: Discussionmentioning
confidence: 96%
“…An extensive retrospective study 25 that evaluated the relationship between the presence of H. pylori antibodies in the blood and gallstones found no relationship between the rates of gallstones in H. pylori -positive patients overall, but a significant negative correlation was observed in individuals aged <45 years. The same study identified a significant relationship between gallbladder polyps and H. pylori -positivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that H. pylori might infect the biliary tract and cause hepatobiliary pathologies ranging from chronic cholecystitis and primary sclerosing cholangitis to GBC and CC [11,12]. To date, several meta-analyses were conducted in order to explore the association between Helicobacter spp.…”
Section: Introductionmentioning
confidence: 99%